2000
DOI: 10.1177/030802260006300808
|View full text |Cite
|
Sign up to set email alerts
|

Basic Grade Occupational Therapists: A Descriptive Evaluation of a Community Rotation Scheme

Abstract: Difficulties in recruiting staff to National Health Service (NHS) facilities have been noted in the literature and, among occupational therapists, this problem is particularly acute in urban areas. One inner-city NHS trust responded to this difficulty by establishing a rotation scheme that allowed basic grade occupational therapists to gain experience in a range of community-based posts. There appear to be few precedents for such a scheme and the experience of newly qualified staff in non-traditional settings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…These findings are in line with previous research on allied health provider job satisfaction in LTC. Greater autonomy [ 16 , 18 ] and ability to contribute to decision making [ 17 ] have long been shown to promote job satisfaction among allied health professionals. For example, Tourangeau and colleagues [ 60 ] found that higher job satisfaction among allied healthcare providers was associated with higher psychological empowerment and higher sense of personal accomplishment, and that lower levels of autonomy on the job were positively correlated with intention to leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with previous research on allied health provider job satisfaction in LTC. Greater autonomy [ 16 , 18 ] and ability to contribute to decision making [ 17 ] have long been shown to promote job satisfaction among allied health professionals. For example, Tourangeau and colleagues [ 60 ] found that higher job satisfaction among allied healthcare providers was associated with higher psychological empowerment and higher sense of personal accomplishment, and that lower levels of autonomy on the job were positively correlated with intention to leave.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional nature of our analysis limits ability to assess whether temporal changes in organizational context affect allied healthcare providers’ job satisfaction. Further, as this was a secondary analysis, the data did not contain all of the variables of interest identified in the literature, e.g., levels of administrative duties [ 17 ], contextual variables such as less routinization [ 18 ], satisfaction with residents and residents’ families [ 16 ], pay and benefits (particularly as compared to those working in other sectors) [ 93 95 ], and opportunities for promotion and career advancement [ 18 , 96 ]. Additionally, some of the scales used in the original study with established reliability, when administered to healthcare aides [ 54 ] and nurses [ 53 ] in LTC, displayed lower alpha scores of <.70 when administered to allied healthcare providers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, participants identified that the availability of support had a major positive impact on their professional practice. While the lack of professional support can sometimes help to develop skills out of necessity, ultimately there is the potential for frustration and decreased job satisfaction 20 …”
Section: Discussionmentioning
confidence: 99%
“…Laura Quick, 1 Kirsty Forsyth 2 and Jane Melton 1 within 2 years (Brasler 1993, Casey et al 2004, Marcum and West 2004. In the occupational therapy literature, it is noted that new graduates have changed post when the perceived level of support is inadequate for their needs (Parker 1991, Ryrie et al 2000, Tryssenaar and Perkins 2001.…”
Section: From Graduate To Reflective Practice Scholarmentioning
confidence: 99%
“…In this climate, it is important to enable new graduates to develop their knowledge, skills and confidence to meet these exacting demands, in an effective and supportive environment. This is of particular importance because there is growing concern over the retention of new graduates (Parker 1991, Brasler 1993, Ryrie et al 2000, Lee and MacKenzie 2003, Casey et al 2004, Marcum and West 2004. If new graduates do not receive effective support to complete the transition to a competent professional, then the concern is that they may choose to leave the profession and /or seek new roles (Parker 1991, Brasler 1993, Ryrie et al 2000, Casey et al 2004.…”
Section: Introductionmentioning
confidence: 99%